Domestic Plastic Waste Generation in Rural Area of Thai Do Commune, Thai Thuy District, Thai Binh Province - Thi Phuong Anh, Duong; Trung Thang, Nguyen; Thi Ha, Nguyen; Truong Huynh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1DO - 10.25073/2588-1094/vnuees.4998, 2024)
The case study was conducted to evaluate the current situation of plastic waste generation from households in Thai Do commune, Thai Thuy district, Thai Binh province. The survey results show that the average plastic waste generation rate per capita in Thai Do commune is 0.04 kg/person/day. Accordingly, the total average mass of plastic waste generated in Thai Do commune is 268.4 kg/day, accounting for about 14.18% of the total mass of generated domestic solid waste. The composition of plastic waste generated in Thai Do commune is mainly plastic packaging containing/wrapping food (37%) and plastic bags with straps (29%). Domestic solid waste is classified by households into plastic recyclable waste and non-plastic recyclable wastes (such as paper, metals, etc.), the latter is typically for sale of scrap. Remaining plastic waste is collected with the rest of domestic solid waste two to three times/week, then is transported to the central waste treatment site of the commune in Tan Lap village for incineration. At the central treatment site, recyclable plastic waste continues to be classified by workers operating the treatment process. These plastic waste data will be the scientific basis to recommend approaches and solutions to reduce the plastic waste generated from the domestic solid waste in the rural area in Thai Do commune, Thai Thuy district, Thai Binh province.